Evolution of deformation styles at a major restraining bend, constraints from cooling histories, Mae Ping fault zone, western Thailand - Morley C.K. (2014)
The c. 500-km-long Mae Ping fault zone trends NW-SE across Thailand into eastern Myanmar and has probably undergone in excess of 150 km sinistral motion during the Cenozoic. A large, c. 150-km-long, restraining bend in this fault zone lies on the western margin of the Chainat duplex. The duplex is a low-lying region dominated by north-south-trending ridges of Mesozoic and Palaeozoic sedimentary, metamorphic and igneous rocks, flanked by flat, post-rift basins of Pliocene-Recent age to the north and south. A review of published cooling-age data, plus new apatite and zircon fission-track results indicates that significant changes in patterns of exhumation occurred along the fault zone with time. Oldest uplift and erosion (Eocene) occurred in the Umphang Gneiss region, west of an inferred thrust-dominated restraining-bend setting. From 36 Ma to 30 Ma, exhumation was strongest north of the duplex, along the NW-SE-trending segment of the fault zone at the (northern) exiting bend of the Chainat duplex. This region of the fault zone is characterized by a mid-crustal level shear zone 5-6 km wide (Lan Sang Gneisses), that passes to the NW into an apparent strike-slip duplex geometry. The deformation is interpreted to have occurred during passage around the northern restraining bend, which resulted in vertical thickening, uplift, erosion and extensional collapse of the northern side of the shear zone. This concentration of deformation at the bends at the ends of the restraining bend is thought to be a characteristic of strike-slip-dominated restraining bends. Following Late Oligocene-Early Miocene extension, there is apatite fission-track evidence for 22-18 Ma exhumation in the Chainat duplex, that coincides with a phase of inversion in the Phitsanulok Basin to the north. The Miocene-Recent history of the Chainat duplex is one of minor sinistral and dextral displacements, related to a rapidly evolving stress field, influenced by the numerous tectonic reorganizations that affected SE Asia during that time. © The Geological Society of London 2007.